Virtuous cycles of learning: Using formative, embedded, and diagnostic developmental assessments in a large-scale leadership program - and Stein, Z.; Dawson, Theo; Van Rossum, Zachary; Rothaizer, Joel; Hill, S. (Journal of Integral Theory and Practice, 2014)
This article presents preliminary results from a series of ongoing action-research projects involving the use of embedded diagnostic developmental assessments (called LectaTests™) in leadership education contexts. These findings are presented to support a particular metatheoretical approach to learning and education in which embedded assessments form a crucial part of ongoing virtuous cycles of action, feedback, support, and learning. We present two types of evidence. First, we compare developmental growth across eight program evaluations in which LectaTests were and were not embedded. Second, we examine how embedding LectaTests in a large-scale leadership development program affected the growth of managers and their direct reports. We review these findings with an eye toward detecting the benefits of using developmental assessment as embedded diagnostics alongside their use as research instruments. We begin by using Integral Theory to structure a discussion about the ideal function of developmental assessments in educational contexts.